Adjusting coherence length of expanded graphite by self-activation and its electrochemical implication in potassium ion battery. (February 2023) - Li, Weifeng; Peng, Daoling; Huang, Wenxin; Zhang, Xiaoshan; Hou, Zhipeng; Zhang, Wenli; Lin, Bixia; Xing, Zhenyu
Abstract: As a cost-effective and well-developed material, graphite is a promising anode material for potassium ion battery due to its high capacity, high tap density, high conductivity and plateau-typed charge curve characteristic. However, graphite suffers from severe capacity fading and poor rate capability. The related research mainstream focuses on electrolyte or binder, aiming at a more robust passivation layer. In contrast, it is not common to transform or modify graphite directly, due to its rigid structure and inert property, which is resistant to gentle chemical treatment. Adjusting coherence length of graphite and its effect on cyclability and rate ability has not been studied yet. Herein, we come up with a strategy of crippling the crystallinity of graphite by strong oxidation first, followed by adjusting coherence length under different pyrolysis temperatures. In the battery test, the expanded graphite pyrolyzed at 750 °C delivers a reversible capacity of 303 mAh/g at a current density of 10 mA/g and 105 mAh/g at a current density of 1000 mA/g. In the long cycling test, a capacity of 160 mAh/g can be maintained after 1000 cycles, with a capacity decay of only 0.02% per cycle. Based on the analysis between coherence length and battery performance, we find that decreasing the coherence length along ab plane contributes to improving rate capability, from both intercalation and pseudo capacitance perspective. Moreover, decreasing the coherence length along c axis contributes to the cyclability. Graphical abstract: Image 1